Identifikasi Komponen 4A terhadap Potensi Pengembangan Objek Wisata Kampar di Kecamatan Tembilahan Hulu Kabupaten Indragiri Hilir Provinsi Riau - Yuliana, Yuliana; Mariya, Sri (Lembaga Yasin AlSys, 2024)
The objective of this study is to analyze the tourism potential of Kampar Tourist Attraction in Tembilahan Hulu District, Indragiri Hilir Regency, Riau Province, and to eval_uate the application of the 4A components in its development. Specifically, this research aims to assess the aspects of Attraction, Accessibility, Amenities, and Ancillary services applied to the tourist site. This qualitative research employs a field research approach with a descriptive methodology. Information was collected using purposive sampling techniques, involving interviews, observations, and literature reviews. Eight informants, including managers, vendors, and tourists at Kampar, were interviewed. The findings reveal that Kampar Tourist Attraction meets the four main 4A components (Attraction, Accessibility, Amenities, Ancillary). The natural attraction potential at Kampar is strong, with artificial facilities such as a swimming pool and boat rides. Accessibility is rated well due to its strategic location and adequate parking facilities. While amenities like accommodation and food variety are sufficient, there is still a need for improvements in dining facilities. On the other hand, ancillary services such as self-management and digital marketing demonstrate effectiveness. However, some components still require enhancement and development. The analysis provides a detailed view of the current conditions at the tourist site and identifies areas for improvement, offering recommendations for better development of the tourist attraction.